(untitled) (Fiep Bulletin - online, 2015)
The amplitude of the Eletromiographic signal (EMG) has been used to correlate the motor units to its strength production, during a training period. The validity of this mensuration is disputed due to some limitations of the Surface Eletromiography techniques, which could lead to the difficulty in reproducing the EMG signal in different acquisitions. Therefore the objective of this paper was to verify the reliability of the amplitude of the EMG signal of the vastus lateralis muscle (VL) in the right thigh, in different occasions, during maximum and submaximum knee extensors isometric actions. Three people performed the following protocol: execution of 3 maximum voluntary isometric contractions (MVCs) during 3s each, with later execution of submaximum actions (20, 40, 60 and 80% of the MVC), calculated considering the MVC of the highest torque peak. Each submaximum contraction (SC) lasted 4s and was kept through a visual feedback (oscilloscope). Between each MVC and among the SC a 2min gap was given. Parallel to the actions, EMG signal of the VL muscle was obtained through the surface electrodes put on the muscle venter longitudinally to the direction of the fibers. A reference electrode was positioned in the tuberosity of the tibia. To attest the same position among the sampling the site of the electrodes was marked with a pen for retroprojector. The same protocol was performed after 48hs for reliability analysis. Such analysis was made through Pearson correlation, with significance p < 0.05. After signal processing and comparison of root mean square values, obtained in the test and re-test, it was found a high correlation among these values (r = 0.972, p < 0.01). These results suggest the reliability of the EMG signal, which would make its usage available for investigations that aim at comparing its amplitude in acquisitions performed in different occasions.